The relationship of functional grammer theory in getting grammar information for students . - مؤيد فاضل سرى; خلباص الزاملي حسن (Al-Adab Journal, 2018)
The relationship of functional grammar theory in getting grammar information for students. The functional grammar theory is a goal in itself because the goal is not training it but carrying it as a mean to teach students language skills through which he or she can communicate with people easily and improving his language abillity . The functional grammar theory is helping the students get the four major language skills : listening , speaking , reading and writing that are used in language learning process that should be used correctly by the students for getting across their message and be able to use the language easily and well . The grammatical concept is a grammatical terminator with a verbal meaning that defines its meaning, and shows the characteristic or the restriction that falls under what is consistent with the significance or characteristics, and comes out of it does not agree with it. The concept of grammar is a picture of abstract mentality that the student formulate of the word and its structure and relationship with others. It has a rule that adjusts its characteristics and adjectives to indicate the grammatical section to which it belongs so it is easier to distinguish them from others and to judge the anomaly for the distinctly distinct . Scholars and researchers have taken different directions in interpreting the learning of the concept, according to the theories or models of learning that they believe in as it is, and it has a rule that adjusts its characteristics and attributes to indicate the grammatical section to which it belongs as in the case is in the Hilda Taba and Frier’s model. It is necessary to use a variety of strategies that help to filter those concepts in their minds. Therefore, the need for educational strategies that focus on teaching concepts that help to organize the student’s cognitive structure and shape, and to be able to learn more quickly than before. Sothe concepts are increasingly concerned to help the learner cope with the challenges of the accelerated cognitive explosion. Therefore, the process of acquiring them has become one of the main goals that educators seek to achieve because they summarize the many contradictory and interrelated information gathered in the pillars of knowledge and its key in the past, the present and the future in the life of the learner (Titi, 2004, p. 23).